2002
DOI: 10.1097/00001573-200201000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Do ACE inhibitors or angiotensin II antagonists reduce total mortality and arrhythmic mortality? A critical review of controlled clinical trials

Abstract: ACE-inhibitors (ACE-I) represent effective drugs more and more widely used in acute myocardial infarction (AMI) patients, in post AMI patients and mainly, today, in CHF patients.A complete review of the scientific literature and of all the randomized controlled clinical trials (RCTs), where ACE-I have been tested directly or in association with other drugs, have been performed. ACE-I effects on total mortality (TM) and arrhythmic mortality (AM) and other composite clinical endpoints have been evaluated. It is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Despite recent advances in the treatment and the primary prevention of heart failure (1,115,168,178), the long-term prognosis for patients who present with this diagnosis remains dismal and the economic burden to the health care system is huge (47,133). In this perspective, a consideration of the role of the brain may be critically important in the development of effective therapeutic strategies.…”
Section: Translational Aspectsmentioning
confidence: 99%
“…Despite recent advances in the treatment and the primary prevention of heart failure (1,115,168,178), the long-term prognosis for patients who present with this diagnosis remains dismal and the economic burden to the health care system is huge (47,133). In this perspective, a consideration of the role of the brain may be critically important in the development of effective therapeutic strategies.…”
Section: Translational Aspectsmentioning
confidence: 99%
“…The ELITE study, which compared losartan versus captopril in patients with NYHA class II or III HF who had not previously received an ACE inhibitor, showed a lower rate of both all-cause mortality and SCD under losartan [42]. However, the far larger ELITE II study found a non-significant trend to more SCD with losartan [43], with similar findings in the OPTIMAAL trial of 5,477 patients with acute MI and HF [44]. ARBs are thus currently considered an alternative therapy in HF patients who cannot tolerate ACE inhibitors.…”
Section: Raas Inhibition and Scdmentioning
confidence: 69%
“…108 For example, in CONSENSUS there was a 50% relative risk reduction in death caused by progressive HF, but no change in sudden cardiac death after treatment with enalapril. 3 Aldosterone blockade reduces the risk of both atrial and ventricular arrhythmias, which may partly explain the reductions in sudden cardiac death observed in clinical trials.…”
Section: The Raas and Hf Pathophysiologymentioning
confidence: 99%